Listeria monocytogenes استخدام طريقة حديثة في الكشف عن بكتريا التسمم الغذائي - مطلك خميس حبيب; جعفر محمد موسى; فوزي عمار; عباس عبد الخالق (Al-Nahrain Journal of Science, 2013)
This study was conducted for detection of Listeria monocytogenes using recent method called Clearview for some imported types of cheeses. Results showed that samples of cheeses were contaminated with Listeria monoicytogenes in different percentages (10%) of the cheese type Tehama,(10%) of cheese type Presedant, (5%) of the cheese type Mozhurella while Lafschri samples have not any statement of contamination with this bacteria. Clearview is a recent method used for isolatation and identification of Listeria monocytogenes which reduced detection time to three days compared to seven days with the rotine method.The antibiotics sensitivity test revealed that bacteria was resistant to pastracin and triymocsoxal(100%) and sensitive to penicillin and amoxycilin (50%).